Gastroenteropancreatic Neuroendocrine Tumors. (8th October 2018) - Cives, Mauro; Strosberg, Jonathan R.
Abstract: Neuroendocrine tumors (NETs) are heterogeneous malignancies arising from the diffuse neuroendocrine system. They frequently originate in the gastroenteropancreatic (GEP) tract and the bronchopulmonary tree, and their incidence has steadily increased in the last 3 decades. Fundamental biologic and genomic differences underlie the clinical heterogeneity of NETs, and distinct molecular features characterize NETs of different grades and different primary sites. Although surgery remains the cornerstone of treatment for localized tumors, systemic treatment options for patients with metastatic NETs have expanded considerably. Somatostatin analogs have demonstrated both antisecretory and antitumor efficacy. Peptide receptor radionuclide therapy with lutetium‐177 dotatate ( 177 Lu‐DOTATATE) has been approved for advanced GEP‐NETs. The antitumor activity of everolimus has been demonstrated across a wide spectrum of NETs, and the antiangiogenic agent sunitinib has been approved for pancreatic NETs (pNETs). Chemotherapy with temozolomide and capecitabine has recently demonstrated an unprecedented prolongation of progression‐free survival in a randomized trial of pNETs. Multiple retrospective series have reported the efficacy of liver‐directed therapies both for palliating symptoms of hormone excess and for controlling tumor growth. Telotristat, an oral inhibitor of tryptophan hydroxylase, has been shown to reduce diarrhea in patients with carcinoid syndrome. Defining the therapeutic algorithm and identifying biomarkers predictive of response to treatments are among the main priorities for the next decade of research in the NET field.